If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 3x + 7 Reorder the terms: 0 = 7 + 3x Solving 0 = 7 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 0 + -3x = 7 + 3x + -3x Remove the zero: -3x = 7 + 3x + -3x Combine like terms: 3x + -3x = 0 -3x = 7 + 0 -3x = 7 Divide each side by '-3'. x = -2.333333333 Simplifying x = -2.333333333
| 57+p=23 | | (3x-8)(4x-2)= | | -8w+3(w-4)=23 | | 5-8x=20+3(2.3x) | | 4(3x+8)=44+64 | | 2x+19=5x+22 | | 2=2(v+7)-4v | | 11p+q-9p+19q= | | 5x+3x=100 | | 10-(x-3)=x+(3x-7) | | H(3)=3(3)+2 | | 5n^2-10n+4=0 | | x^4=-64 | | 6x^8+26x^5-26x^2=0 | | -(-9+4x)=2-4(9+x) | | H(-1)=3(-1)+2 | | 3x+20=x+16 | | x^2+7x-45=3(x-8) | | (4x+10)+7x= | | -5x+1=3x+11 | | 2x^2+19x-18=0 | | 10+2x=6+3 | | (2m-12)-(-9m-7)= | | (x+(3+5i))(x+(3-5i))=0 | | (x+(3+5i))(x-(3-5i))=0 | | 5(7-w)+5w=36 | | 3(6u+8)=16u+20 | | 3x-12=8+3x | | √(12y)1/2 | | (x+5)+x=90 | | 15*3.1415926535897932384626433832795= | | 2z(2z+1)(5z-4)= |